Pulmonary benign metastasizing leiomyoma: a case report and literature review - Chen, Shi; Liu, Rui-Ming; Li, Tian (Journal of Thoracic Disease, 2014)
Benign metastasizing leiomyoma (BML) is a rare condition that occurs in all age groups and that is particularly prevalent among women of late childbearing age. All patients have a history of uterine leiomyoma and/or myomectomy, often associated with distant metastases from the uterus, which commonly occurs in the lung. We report the case of a 32-year-old young woman suffering from chest stuffiness, labored respiration and weakness after a myomectomy performed one month earlier. The chest CT showed a diffuse miliary shadow in both sides of her lungs, but serum tumor markers such as CA125, CA199, carcinoembryonic antigen (CEA), neuron specific enolase (NSE), and CYFRA21-1 were normal. The patient underwent a lung biopsy by thoracoscopic surgery after four weeks of anti-TB treatment; there were no significant changes in the chest CT. H&E staining showed that the tumor cells had characteristics of smooth muscle cell differentiation. Immunohistochemical staining showed a low tumor cell proliferation index, which indicated that the likelihood of a malignancy was not high. There was no expression of CD10, indicating a diagnosis of pulmonary benign metastasizing leiomyoma (PBML). Smooth muscle actin (SMA) and desmin as specific markers of smooth muscle and the estrogen receptor (ER) and progesterone receptor (PR) were all strongly positive, which is characteristic of PBML. The patient was given the anti-estrogen tamoxifen for 3 months. With no radiological evidence of disease development and further distant metastasis, the patient will continue to be followed.